Perancangan Sistem Informasi Data Radio Inventory Berbasis Web pada PT Nusa Halmahera Minerals - Sujiman, Iswahyuni; Sitokdana, Melkior N.N. (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2024)
PT Nusa Halmahera Minerals is a gold mining business with an underground system in a very large location. Because of the large development, more and more data is managed every day with location points between office buildings, mines, and each employee is far apart. This causes data collection to be less real time and there are problems in separating data that has been used from that which has not been used in radio searches. The aim of this research is to create an information system that is able to solve this problem so that in the future all data can be accessed in one system so that employees can access it easily so that the data they have is used more efficiently and is easily accessed from any point of work location. The methodology of this research is interviews and direct observation in the field to analyze system requirements and to create a system using the waterfall method up to the testing stage. With the results of system analysis, UML modeling, and designed activity diagrams, this research succeeded in building an information system website that manages radio inventory data which can be accessed by any employee who has a user ID.